2022
DOI: 10.1371/journal.pone.0264627
|View full text |Cite
|
Sign up to set email alerts
|

Superior effect of allopurinol compared to febuxostat on the retardation of chronic kidney disease progression

Abstract: Background Although hyperuricemia is associated with chronic kidney disease, whether and how it should be managed for renoprotection remains debatable. Thus, we investigated whether allopurinol and febuxostat, the most frequently used urate-lowering treatments, have differential renoprotective effects on chronic kidney disease. Methods Incident users of allopurinol and febuxostat were identified from two tertiary referral centers. One-to-one propensity score matching between the allopurinol and febuxostat gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…However, the choice between febuxostat and allopurinol for the treatment of hyperuricemia remains debatable. Some studies have reported no difference in CV outcomes between febuxostat users and allopurinol users [18,19,23,[28][29][30][31][32][33][34], whereas other studies have suggested that febuxostat increases the risk of CV-related mortality [26,[35][36][37]. The rates of allcause mortality were also higher among febuxostat users compared to those using allopurinol.…”
Section: Introductionmentioning
confidence: 99%
“…However, the choice between febuxostat and allopurinol for the treatment of hyperuricemia remains debatable. Some studies have reported no difference in CV outcomes between febuxostat users and allopurinol users [18,19,23,[28][29][30][31][32][33][34], whereas other studies have suggested that febuxostat increases the risk of CV-related mortality [26,[35][36][37]. The rates of allcause mortality were also higher among febuxostat users compared to those using allopurinol.…”
Section: Introductionmentioning
confidence: 99%